Psoriasis New Research - Aghaei, Shahin (IntechOpen, 2022)
Psoriasis is a chronic skin disease that starts with lesions that appear red, thick, scaly, and itchy with bilateral and symmetrical distribution. The lesions are most often seen in the scalp, elbows, knees, and genitalia. The extent of the lesions is not always limited to these areas, and in some cases, it may involve larger parts of the skin, as well as nails and joints in some cases. This book presents a comprehensive overview of psoriasis, including clinical aspects, differential diagnosis by dermoscopic devices, comorbidities, immune system changes, methotrexate therapy, and topical innovative molecular targeted therapeutics.